The social medical thought of Ernesto Che Guevara: His presence in the Cuban socio-medical paradigm - Blanca Rosa Garcés Garcés; Lian Roque Roque; Ana María Molina Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Ernesto Che Guevara´s personality is recognized worldwide for his contribution to the struggle of the peoples, his ethics and his revolutionary principles which have left their mark on the social economic and cultural life, politics, of different nations of the world. An insufficiently studied aspect of his work, however, has been his thinking and actions in favour of the development of social medicine which grants a leading role to the social factors in the origin and development of health and disease so as the political and governmental action in the areas of prevention, promotion, rehabilitation and medical care. These ideas of Che were made up throughout his life, long before starting his medical studies, were consolidated during the guerrilla struggle in the Sierra Maestra and became belief in his practical behaviour, first, during the revolutionary struggle and then after the triumph in 1959 in Cuba. In the social medical thinking of Che, they are contained the guiding principles and the conceptual and practical bases of the Cuban socio-medical paradigm, which are valid in the conception of familial medicine and in the formation of the Cuban familial doctor. This work is aimed at determining the main elements of the social medical thinking of Ernesto Che Guevara and their theoretical contribution to the conformation of the Cuban socio-medical paradigm.